The impact of functional efficiency of ZOL patients on the workload of nurses - Katarzyna Tomaszewska; Judyta Światlak; Alicja Kłos; Kinga Przybyszewska (Kazimierz Wielki University, 2019)
The specificity of long-term care facilities is to take care of people who are unable to take care of their own existence for health reasons. Most often they are elderly people, with a significantly limited ability to function independently in terms of satisfying basic life needs, unable to self-care. The work of nursing staff is one of the most difficult ones with a high level of responsibility, which often requires constant and full availability, coping with ethical dilemmas and imperfections of work organization. An indispensable element of the work of nursing staff is a significant workload, often associated with functioning among the sick and suffering people. An elementary assessment of functional efficiency is a significant, though simplified diagnostic process for the patient. In Care and Treatment Facilities (ZOL), it is the basis for determining the patient's condition and its deficit of independence in everyday life Purpose of research The aim of the study was to assess the impact of the level of functional efficiency of Care and Treatment Facilities on the workload of the nurse. Material and methods The research was conducted among 92 nurses employed in the Care and Treatment Facilities (ZOL) of the Podkarpackie Voivodeship from September to November 2017. The questionnaire used in this paper was a survey, which contained 30 single and multiple-choice questions. The next stage of the study was the analysis and comparison on the Barthel scale of patients of ZOL, which were examined in this work. The research was done according to the Barthel scale. What is more, it covered 206 residents of Care and Treatment Facilities in the Podkarpackie region. For the purpose of this work, the following tests were used for questions on nominal scales to verify hypotheses: V Kramer (2x3, 4x5 tables etc.), Phi (2x2 tables) and Tb- or Tc-Kendall. During the statistical analysis of the collected material, p